Effects of water flow treatment on muscle quality, nutrient composition and volatile compounds in common carp (Cyprinus carpio) - Lei Wang; Lingran Wang; Chang Liu; Di Feng; Jintai Huang; Zhan Jin; Fangran Ma; Jiaxin Xu; Yuyue Xu; Meng Zhang; Miao Yu; Hongxia Jiang; et al. (Food Chemistry: X)
This study explored the effects of water flow on the muscle quality, nutrient composition, and volatile compounds in Cyprinus carpio. Fish were exposed to three treatments: sustained water flow (SG, 1 bl/s, 24 h/d), intermittent water flow (IG, 1 bl/s, 8 h/d), and control group (CG, 3 cm/s). Results indicated that SG improved water-holding capacity, muscle fiber density, hardness, and chewiness, while IG enhanced gumminess, springiness, and resilience. Nutritionally, CG exhibited higher crude lipid content and the highest levels of ΣSFA. Conversely, SG showed elevated ∑EPA + DHA and ω-3 fatty acid levels compared to IG. Volatile compound analysis demonstrated that CG contained higher levels of aldehydes and alcohols, associated with off-flavors, whereas IG and SG produced fresher and sweeter aroma profiles, enhancing sensory quality. These findings provide valuable insights into improving the muscle quality, nutritional value, flavor characteristics, processing, and preservation of common carp through water flow treatment.